81.7k views
2 votes
Use the zero product property to solve the equation. (4k+5)(k+7)=0

2 Answers

4 votes

Answer:

brooo just did test -5/4 or 7

Explanation:

bc -5/4 x 4x equals 5 so basicaly -5 - 5 equals fuqing 0 and that -7 minus 7 equals 0 and 0 x0 equal ummmm loading.......

0 horray

User Whatwhatwhat
by
5.5k points
0 votes
the zero product property tells us that if we have
xy=0, then we can assume that x and y both equal 0

so

(4k+5)(k+7)=0
we can assume that 4k+5=0 and k+7=0
so

4k+5=0
minus 5 both sides
4k=-5
divide both sides by 4
k=-5/4

k+7=0
minus 7 both sides
k=-7


k=-5/4 or -7
User Juniel
by
5.9k points